chlamydia trachomatis and HPV coinfections in women with condiloma acuminata - Marcolino, Larissa D.; Polettini, Jossimara; Tristão, Andréa R.; Marques, Mariângela Esther A.; Candeias, João Manuel G.; Vela, Rodrigo Alessandro R.; Silva, Márcia G. Silva (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: Chlamydia trachomatis is worldwide recognized as one of the most prevalent sexually transmitted diseases (STD) of bacterial origin, whereas genital Human Papillomavirus (HPV) infection is one of the most important STD caused by virus. Objective: evaluate the coinfection rate of C. trachomatis and HPV in women with condyloma acuminata. Methods: thirty women were included in the study based on clinical and histopa thological diagnosis of condyloma acuminata in vulvar, vaginal or perianal region. The excised lesions were divided into two halves, one was submit ted to a histopathological exam and the other to DNA extraction. C. trachomatis was detected by PCR using CTP1 and CTP2 primers and the HPV DNA was detected by PCR and subsequent typed by PCR with HPV specific primers. Results: the HPV DNA positivity was 100% in all samples. HPV type 6/11 was found in 33.3% of the samples, type 18 in 6.7%, and we also found infection with multiple HPV types in 56.7% of HPV induced lesions, and only one sample (3,3%) was not genotyped. The C. trachomatis positivity in cervical secretions of women with condyloma acuminata was 33.3%. Conclusion: the coinfection rate of C. trachomatis and HPV in women with condyloma acuminata is high and the screen and treat strate gy for chlamydial infection should be incorporated to gynecology routine care in these patients.